Hypersthetic reactions and actual self-perception students at the stage of self-isolation during the COVID-19 pandemic - M. M. Basimov; N. A. Tsvetkova (Вестник университета)
The article contains the results of a survey of Moscow students of both sexes during the quarantine period associated with the COVID-19 pandemic. Hypersthetic reactions and self-perception were studied. It is shown that the proportion of students with a high overall level of hypersthetic reactions was 5.8 %, with an average – 27.5 %, with a low – 66.7 %. All private indicators of this parameter are registered in the low range of values with a tendency to the average level. The most pronounced reaction turned out to be “paying attention to different situations, events or stimuli that I had completely ignored before.” The results of a comparative analysis of data by gender are presented; girls have a significantly higher overall level of hypersthetic reactions. All indicators of actual self-perception turned out to be moderately pronounced, indicating its adequacy. Intersex differences were found in the assessments of “free” and “healthy”. Attention was drawn to the fact that the Pearson correlation analysis did not show a connection between hypersthetic reactions and self-perception - they were identified using the method of statistical relationships research within the framework of the synergetic approach and the nonlinear psychology of M.M. Basimov.